1985
DOI: 10.1128/iai.47.1.142-148.1985
|View full text |Cite
|
Sign up to set email alerts
|

Decreased protective efficacy of reduced and alkylated human immune serum globulin in experimental infection with Haemophilus influenzae type b

Abstract: Conventionally prepared immune serum globulin frequently produces severe side effects when administered intravenously. A modified preparation in which 4 to 5 interchain disulfide bonds have been reduced and alkylated has been made for intravenous use. However, reduction and alkylation may affect Fc-mediated functions of immunoglobulin G, particularly its ability to fix complement by the classical pathway. To determine whether reduction and alkylation alters the protective activity of immune serum globulin in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…Infant rats that received single-donor human IgG or IgM Hib CP antibody in doses giving serum antibody levels of 200 to 2,000 ng/ml were protected from Hib bacteremia, meningitis, and death (Table 1), consistent with previous findings (16)(17)(18)(19). Administration of CoVF, however, abrogated the protective effects of both IgG and IgM Hib CP antibody even when levels in serum were many times the minimum protective level.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Infant rats that received single-donor human IgG or IgM Hib CP antibody in doses giving serum antibody levels of 200 to 2,000 ng/ml were protected from Hib bacteremia, meningitis, and death (Table 1), consistent with previous findings (16)(17)(18)(19). Administration of CoVF, however, abrogated the protective effects of both IgG and IgM Hib CP antibody even when levels in serum were many times the minimum protective level.…”
supporting
confidence: 87%
“…A streptomycin-resistant mutant of Hib Eagan (E-1) was freshly subcultured for each experiment and used in the animal experiments. Inocula for animal challenge were prepared as previously described (18,19), and cultures of tail blood and spinal fluid of rats were grown on supplemented brain heart infusion agar containing 40 ,ug of streptomycin per ml and 5 U of bacitracin per ml to inhibit growth of contaminants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hetherington and Giebink reported that the opsonic activity of IgG prepared by chromatography with DEAE-Sephadex is greater than that of reduced and alkylated IgG against Staphylococcus aureus and Streptococcus pneumoniae (2). Schreiber et al also reported that pH 4-treated IgG is more protective in infant rats against Haemophilus influenzae type b than reduced and alkylated IgG (8). In this study, IgG separated from whole serum by QAE-Sephadex appeared to be even more protective in vivo against the type III GBS than IgG prepared from Cohn fraction II that had been reduced and alkylated or treated at pH 4.…”
supporting
confidence: 51%
“…S-sulfonation [13] or S-alkylation following reduction [14] under mild conditions cleaves the interchain, but not the intrachain, disulfide bonds of IgG, resulting in decreased activity of some effector functions, such as complement activation. Recently, Dall'Acqua et al [15] showed that recombinant IgG molecules without inter-H chain disulfide bonds had decreased antibody-dependent cellular cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%